Plants and Climate Change - Rozema, Jelte; Aerts, Rien; Cornelissen, Hans (Tasks for Vegetation Science,, 2006)
The book Plants and Climate Change focuses on how climate affects or affected the biosphere and vice versa both in the present and past. The chapters describe how ecosystems from the Antarctic and arctic and from other latitudes respond to global climate change. The book covers papers highlighting plant responses to atmospheric CO2 increase, to global warming and to increased ultraviolet-B radiation as a result of stratospheric ozone depletion. Depending on how and how well plant responses to increased temperature, atmospheric CO2 and ultraviolet-B have been preserved in the (sub)-fossil record, past climates and past atmospheric chemistry may be reconstructed. Pollen and tree-ring data reflect plant species composition and variation of temperature and precipitation over long or shorter time intervals. In addition to well preserved morphological and chemical plant properties, new analytical techniques such as stable isotopes are becoming increasingly important in this respect. The development and validation of such biotic climate and environment proxies build a bridge between biological and geological research. This highlights that plant-climate change research is becoming a multi- and transdisciplinary field of relevant research. Reprinted from Plant Ecology, 182:1-2 (2006).